Association between opioid abuse and COVID-19 susceptibility: a propensity score matched study - Mojtaba Hedayatyaghoobi; Mehdi Azizmohammad Looha; Arman Shafiee; Kyana Jafarabady; Omid Safari; Amirhesam Alirezaei; Mahmood Bakhtiyari (BMC Infectious Diseases, 2023)
Abstract Background Opioid use disorder (OUD) has been associated with adverse health outcomes, and its potential impact on COVID-19 outcomes is of significant concern. This study aimed to assess the susceptibility and clinical outcomes of hospitalized COVID-19 patients with OUD using a propensity score-matched design. Methods A historical cohort study was conducted in Alborz province, Iran, during the early months of the COVID-19 pandemic. Patients aged 18 years and above with confirmed COVID-19 were included in the study. OUD was defined as a compulsive urge to use opioids or opioid-derivative drugs. Non-opioid abusers with COVID-19 were selected as the control group. Data on demographics, clinical characteristics, laboratory factors, comorbidities, and vital signs were collected. Propensity score matching (PSM) was used to balance the groups and assess the impact of OUD on ICU admission, mortality, the need for intubation, and the severity of pulmonary involvement on CT scans. Results A total of 442 patients were included in the study, with 351 discharged and 34 deceased. The PSM analysis showed that OUD was not significantly associated with ICU admission (OR: 1.87, 95% CI: 0.22–2.91, p = 0.631). However, opium users had an increased risk of mortality (OR: 2.38, 95% CI: 1.30–4.35, p = 0.005) and a higher likelihood of requiring intubation (OR: 3.57, 95% CI: 1.38–9.39, p = 0.009) compared to non-opioid abusers. The severity of pulmonary involvement on CT scans did not show a significant association with OUD. Conclusion OUD among hospitalized COVID-19 patients was associated with an increased risk of mortality and the need for intubation. These findings highlight the importance of addressing OUD as a potential risk factor in the management and treatment of COVID-19 patients. Further research is warranted to explore the underlying mechanisms and develop appropriate interventions to mitigate the impact of OUD on COVID-19 outcomes.